Neuroanatomical Differences between First-Episode Psychosis Patients with and without Neurocognitive Deficit: A 3-Year Longitudinal Study - Ayesa-Arriola, Rosa; Roiz-Santiañez, Roberto; Pérez-Iglesias, Rocío; Ferro, Adele; Sainz, Jesus; Crespo-facorro, Benedicto (Frontiers in Psychiatry, 2013)
Background: The course of cognitive function in first episode psychosis (FEP) patients suggests that some individuals are normal or near-normal whereas some cases present a marked decline. The goal of the present longitudinal study was to identify neuroanatomical differences between deficit and non-deficit patients. Methods: Fifty nine FEP patients with neuroimage and neurocognitive information were studied at baseline and 3 year after illness onset. A global cognitive function score was used to classify deficit and non-deficit patients at baseline. Analysis of covarianes and repeated-measures analysis were performed to evaluate differences in brain volumes. Age, premorbid IQ and intracranial volume were used as covariates. We examined only volumes of whole brain, whole brain gray and white matter, cortical CSF and lateral ventricles, lobular volumes of gray and white matter, and subcortical (caudate nucleus and thalamus) regions. Results: At illness onset 50.8% of patients presented global cognitive deficit. There were no significant differences between neuropsychological subgroups in any of the brain regions studied at baseline (all F(1,54) ≤ 3.42; all p ≥ 0.07) and follow-up (all F(1,54) ≤ 3.43; all p ≥ 0.07) time points. There was a significant time by group interaction for the parietal tissue volume (F(1,54) =4.97, p = 0.030) and the total gray matter volume (F(1,54) = 4.31, p =0.042), with the deficit group showing a greater volume decrease. Conclusions: Our results did not confirm the presence of significant morphometric differences in the brain regions evaluated between cognitively impaired and cognitively preserved schizophrenia patients at the early stages of the illness. However, there were significant time by group interactions for the parietal tissue volume and the total gray matter volume during the 3-year follow-up period, which might indicate that cognitive deficit in schizophrenia would be associated with progressive brain volume loss.